2011
DOI: 10.1007/s10198-011-0315-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost–effectiveness of statins revisited: lessons learned about the value of innovation

Abstract: Only a small part of the surplus value generated was appropriated by the producer. A regulatory and reimbursement approach that favors early market access and coverage with evidence development as opposed to long-term trials as a pre-requisite for launch is more attractive from both a company and social perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
(30 reference statements)
2
24
0
Order By: Relevance
“…12 Assuming constant sales of simvastatin through 2018, the Swedish study estimated the overall social value for the period 1987-2018 at 0.7-1.6 billion euros, of which 94-97 percent was consumer value. Related research on antihypertensive, cancer, and HIV drugs has also suggested a large social value that is primarily captured by consumers.…”
Section: Introductionmentioning
confidence: 99%
“…12 Assuming constant sales of simvastatin through 2018, the Swedish study estimated the overall social value for the period 1987-2018 at 0.7-1.6 billion euros, of which 94-97 percent was consumer value. Related research on antihypertensive, cancer, and HIV drugs has also suggested a large social value that is primarily captured by consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The example of medicines in prevention of cardiovascular disease and in breast cancer treatment Life-years gained is also the key outcome measure in studies that have estimated the value of tamoxifen and trastuzumab for the treatment of breast cancer, and lipid-lowering and antihypertensive treatments administered as primary and secondary prevention in cardiovascular disease (Lindgren and Jönsson, 2012, Lundqvist et al, 2013a, Lundqvist et al, 2013b. These studies have included estimates of quality-adjusted life expectancy in the ex-post valuation of new medicines primarily introduced to increase survival.…”
Section: 2mentioning
confidence: 99%
“…Lindgren and Jönsson, (2012) estimated the value of lipid-lowering therapy using simvastatin from its launch in Sweden in 1987 until 2008, based on registry data, and forecasted its continued use to 2028. This study showed a steep increase in the number of individuals commencing treatment with simvastatin when the price was reduced as a consequence of patent expiration(-90%).…”
Section: 3mentioning
confidence: 99%
“…1,2 Statins inhibit 3-hydroxy-3-methylglutaryl CoA reductase (HMGCR) a rate limiting step in the conversion of HMG-CoA to mevalonate, a precursor for several cellular processes. One result of HMGCR inhibition is reduced cholesterol biosynthesis and coupled with increased LDL-receptor mediated sequestration of LDL, statins are effective at lowering circulating LDL-cholesterol levels.…”
Section: Statins Cholesterol and Inflammationmentioning
confidence: 99%